Ensuring Economic Security of Member States of the Eurasian Economic Union in Conditions of Competition of Models of Integration - Alexander A. Maryshev (Евразийская интеграция: экономика, право, политика, 2019)
Today the states of the Eurasian Economic Union practically impossible to independently ensure their economic security. It is necessary either to constantly increase defense spending, or enter into integration formations. Despite the fact that the agenda of the Eurasian Economic Union practically does not discuss security issues, nevertheless, the activity of the EAEU has a “spillover” of economic activities and security issues, the end result of which can be a Large Eurasian partnership.